Long-term moisture conservation and nutrient management improves yield stability and resource use efficiency in pearl millet (Pennisetum glaucum)—mustard (Brassica juncea) system under rainfed ecosystem - S. L. Meena; R. S. Bana; Ramanjit Kaur; Ravi Nirmal; Deepak Singh; Samarth Godara; Teekam Singh; Anchal Dass; Twinkle Jena; Rohan Serawat (Frontiers in Sustainable Food Systems)
Moisture- and nutrient-stress substantially limits the productivity and profitability under rainfed environments; therefore, strategic nutrient and moisture management is obligatory. Present study aims to assess the impacts of diverse moisture-conservation and nutrient-management protocols on yield-stability, system-sustainability, and soil-health in rainfed pearl millet–mustard rotation. Four moisture-conservation systems: control (M1), crop-residue mulch (CRM: 5 t/ha, M2), farmyard manure (FYM: 5 t/ha, M3), and a combination of CRM 2.5 t/ha + FYM 2.5 t/ha (M4); and three nutrient-management practices: control [N1], recommended dose of nitrogen (RDN: 60-40-40 kg/ha, N, P2O5 and K2O, respectively) [N2], and 50% RDN + biofertilizers (Azospirillum + Pseudomonas striata) [N3] were evaluated in split-plot design for 6 years. The study revealed that the M4 and M3 treatments significantly improved pearl millet yield (64.4%−70.7%), mustard yield (25.8%−31.6%), system productivity (35%−41.4%), rainwater-use efficiency (RUE, 35.2%−40.8%), and sustainable yield index (65.5%−81.6%) over control. The system productivity was highest in 2014–15 (6.06 t/ha) and 2019–20 (5.93 t/ha). The RUE reached maxima during 2017–18 (7.27 kg/ha-mm). The M4N3 combination resulted in greatest system productivity (7.64 t/ha), higher available NPK (200, 16.03 and 259.2 kg/ha, respectively) content in top-soil and improved soil microbial-enzymatic activity (dehydrogenase, acid phosphatase, alkaline phosphatase and protease). The integrated approach of CRM + FYM coupled with 50% RDN + Azospirillum + Pseudomonas biofertilizers offers a viable solution for sustainably enhancing productivity in the pearl millet–mustard system under water-limited ecologies. Our studies indicate the potential of adopting organic nutrient-cum-moisture management along with conventional synthetic fertilizers in sustaining the productivity and soil-health in fragile rainfed ecosystems.